2010
DOI: 10.1097/jom.0b013e3181e9edfe
|View full text |Cite
|
Sign up to set email alerts
|

Health Inequalities According to Plant Size—Comparison of Small- and Medium-Sized Enterprises

Abstract: The higher rate of skin impairment in SE might be explained by a lower level of work safety. However, the higher frequency of perceived respiratory symptoms in ME seems to contradict this assumption and except plant size there might exist another potential confounder, especially for breathing impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We adjusted the main analyses for enterprise size and concluded that size did not confound the associations. One previous study investigating the role of plant size for worker health did find different types of health problems in small and medium‐sized enterprises, and concluded that work safety was higher in medium‐sized plants [Baumeister et al, ]. Yet, the study by Baumeister and colleagues focuses on employees and not self‐employed persons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted the main analyses for enterprise size and concluded that size did not confound the associations. One previous study investigating the role of plant size for worker health did find different types of health problems in small and medium‐sized enterprises, and concluded that work safety was higher in medium‐sized plants [Baumeister et al, ]. Yet, the study by Baumeister and colleagues focuses on employees and not self‐employed persons.…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, about 98% of all private enterprises are small (<50 employees), employing up to 35% of the total workforce [Gunnarsson and Josephson, ]. It might be assumed that the self‐employed running bigger companies would have better possibilities to invest in work environment than those working alone or with smaller companies [Baumeister et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated annual costs related to OSDs in Germany exceed €1.5 billion. They are mainly related to work absenteeism and lack of productivity, which particularly affect the competitiveness of small and medium‐sized enterprises .…”
mentioning
confidence: 99%